Human manual distal phalanges from the Middle Stone Age deposits of Klasies River Main Site, Western Cape Province, South Africa. Issue 146 (September 2020) - Grine, Frederick E.; Mongle, Carrie S.; Smith, Shelley L.; Black, Wendy; du Plessis, Anton; Braga, José
Abstract: Two new distal manual phalanges from the Middle Stone Age deposits of Klasies River Main Site are described. One (SAM-AP 6387) likely derives from ray II or ray III, whereas the other (SAM-AP 6388) is from the thumb. Both derive from a late adolescent or fully adult individual. They were recovered by H. Deacon from the same stratigraphic unit (submember W or possibly submember R) of the Shell and Sand Member of Cave 1, which places them between 100 and 90 ka. Both are comparatively small elements, and the possibility that they came from the same hand cannot be discounted at this time. These bones add to the meager and all too fragmentary postcranial human fossil sample from the Late Pleistocene of South Africa. These two specimens provide some additional evidence pertaining to the morphological attributes of the distal phalanges of the Middle Stone Age inhabitants of South Africa. Together with the distal pollical phalanx from Die Kelders (SAM-AP 6402), they are relatively small in comparison with homologs from recent human samples as well as Late Pleistocene specimens from Eurasia. Given their small sizes, the distal pollical phalanges from Klasies and Die Kelders are not dissimilar to Holocene Khoesan homologs. As expected, the Klasies elements differ noticeably from Neandertal homologs, especially in the narrowness of their shafts and distal tuberosities.